# To express: The function G ( x ) = x 1 + x 3 in the form of ( f ∘ g ) ( x ) .

### Single Variable Calculus: Concepts...

4th Edition
James Stewart
Publisher: Cengage Learning
ISBN: 9781337687805

### Single Variable Calculus: Concepts...

4th Edition
James Stewart
Publisher: Cengage Learning
ISBN: 9781337687805

#### Solutions

Chapter 1.3, Problem 44E
To determine

## To express: The function G(x)=x1+x3 in the form of (f∘g)(x) .

Expert Solution

The function G(x)=x1+x3 can be expressed as G(x)=f(g(x)),  where f(x)=x3 and  g(x)=x1+x .

### Explanation of Solution

The given composite function is G(x)=x1+x3 .

Name the expression x1+x as  g(x)=x1+x .

Thus, F(x)=g(x)3

It can be expressed as G(x)=f(g(x)),  as G(x) is a composition of f and g.

Replace g(x) by x to obtain the expression for f(x) .

Therefore, f(x)=x3 .

Hence, it can be concluded that G(x)=x1+x3 can be expressed as G(x)=f(g(x)), where f(x)=x3 and  g(x)=x1+x .

Verification:

The composite function (fg)(x) is defined as follows.

(fg)(x)=f(g(x))

Substitute x1+x for x in f(x) .

f(x1+x)=x1+x3=G(x)

Thus, it is verified that G(x)=x1+x3 can be expressed as G(x)=f(g(x)),  where f(x)=x3 and  g(x)=x1+x .

### Have a homework question?

Subscribe to bartleby learn! Ask subject matter experts 30 homework questions each month. Plus, you’ll have access to millions of step-by-step textbook answers!